Guardians of the galaxy. Vol. 1, Then it's us - Ewing, Al, 1977- (Marvel Worldwide, Inc., 2020)
Once they were a team of misfits. Now they're a family, and they've earned their peace. But the universe is not a peaceful place - and it's only getting worse. The Great Empires are in turmoil. The rule of law is dead. And amid the chaos, the gods of Olympus have returned - harbingers of a new age of war, reborn to burn their mark on the stars themselves. Someone has to guard the galaxy - but who will accept the mission? And will they survive it?